Diagnosis and Treatment of Supraventricular Tachyarrhythmia in Pediatric Population: A Review Article - Hany M Abo-Haded (Open Journal of Pediatrics and Child Health - Peertechz Publications, 2016)
Supraventricular tachyarrhythmia (SVT) is the most common tachyarrhythmia in pediatric patients and accounts for more than 90% of pediatric arrhythmias. As many as 16 different mechanisms of pediatric SVT exist; we focused in this review article on the three most common groups of SVT mechanisms in pediatrics: atrioventricular re-entry tachyarrhythmia (AVRT), atrioventricular nodal reentry tachyarrhythmia (AVNRT), and atrial tachyarrhythmia (AT). Many methods have been implicated in the diagnosis of SVT like full history taking regarding onset and frequency of palpitation, syncope, chest pain, dyspnea, heart failure, drug intake and physical examination. Children with suspected SVT must be subjected to resting 12-lead surface ECG and ECG during the attack. Echocardiography must be done for detection of any structural heart diseases. Moreover, recent techniques like Electrophysiologic study (EPS) is the most defi nitive diagnostic procedure. Many therapeutic strategies like drugs and radiofrequency ablation (RFA) have been succeeded to provide a significant reduction of the risk of SVT, but RFA offers the prospect of cure of the arrhythmia and avoidance of drug-associated side effects. It is often becoming the first line of therapy for many children with SVT, as it has a relatively low morbidity and mortality, and it results in a low rate of recurrence of SVT.